MATHEMATIC MODELLING OF CONCRETE PUMP PRODUCTIVITY ON THE CONCRETE WORK OF CONSTRUCTION PROJECT IN PALANGKA RAYA - Yulin Patrisia; Revianti Coenraad (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
The physical activities in Central Kalimantan Province especially Palangka Raya in the recent years indicates a good development and is cathed by the construction entrepreneur as one of good business opportunities, one of which is ready-mix-concrete company which produce fresh concrete. With this company, the concreting of high building can be done faster with stable concrete quality. In the field, the use of ready mix concrete for high building is equipped with a concrete pump. Concrete pump is an equipment to pump concrete to concreting location, mainly to a location difficult to reach by mixer truck. With concrete pump, concreting can be done faster. However, its productivity depends on the distance and the height of the location, beside the concrete quality itself. The research on concrete pump productivity on the concreting of construction project in Palangka Raya aims to make a mathematic model that is able to predict the relationship between concrete pump productivity and distance and height of the location of concreting. The result shows that there is a strong relationship between productivity with horizontal concreting, which is modelled by the formula (a) Y = 0.642 – 0.09 X1 + E, where Y = productivity (m3/min), X1 = distance (m), E = error; (b) Y = 0.628 - 0.09 X1 - 0.07 X2 + E, where Y = productivity (m3/min), X1 = distance (m), X2 = height (m), E = error